Bioconversion of Glycerol to Docosahexaenoic Acid by Thraustochytrium WB-02 an Indigenous Indonesian Microalga Strain - Basuki, Witono (UI Scholars Hub, 2019)
Glycerol is a by-product of the biodiesel industry, and it can be processed to produce many useful derivatives. This study is aimed at examining the bioconversion of glycerol to docosahexaenoic acid (DHA) using local microalgae. Glycerol to docosahexaenoic acid converting microalgae were obtained from the mangrove area in the coastal sea of Lampung Province. The single colony was then generated by the scratching technique in its isolation and purification process. By using 18S rDNA, a potential strain namely WB-02, was identified as Thraustochytrium sp. Gas chromatog-raphy analysis was performed to identify its product conversion. As a result, Thraustochytrium WB-02 was identified toutilize glycerol as a single carbon source and convert to DHA. A maximum DHA yield of more than 3.4 g/L was ob-tained when the glycerol concentration in the medium was 8%. Thraustochytrium WB-02 was regarded as a potential microalgae resource in producing DHA due to its high level of production.